Keputusan Pembelian Online Pengguna Shopee Ditinjau Dari Celebrity Endors, Brand Trust, dan Online Customer Review: - Della Nurningtyas Romadhona; Sudarwati Sudarwati; Fithri Setya Marwati (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Theipurpose ofithisistudyiwas to determine how theiinfluence oficelebrity endorsers, branditrust, and onlineicustomer reviews variables onithe online purchasingidecisions of Shopee users iniSurakarta. This study uses quantitative researchimethods, withipurposive samplingias a samplingitechnique. Observation, questionnaire, and literature study are data collection techniques. The populationiin thisistudy areiall Shopeeiusersiin the Surakarta area whoseinumber cannot be known, withia sampleiof 100irespondents. Theiresearchimethod uses multipleilineariregressioniwith dataianalysis techniquesiusing validityitest, reliabilityitest, multicollinearityitest, heteroscedasticity test, multiple lineariregressionihypothesisitesting, F test, titest, and determinationitest with SPSSiversioni25 analysis tool.Theiresults inithis studyiindicate that the Celebrity Endorsers, Brand Trust, andiOnline CustomeriReview variables haveia simultaneous effection Shopee online purchasingidecisions in Surakarta and the Celebrity Endorsers, Brand Trust, andi Online Customer Review variables each haveia positiveiand significant influenceion purchasingidecisions online Shopee in Surakarta. Keywords: Purchase Decision, Celebrity Endors, Brand Trust, Online Customer Review